Anticancer Activity of The Ethanol Fraction of Gnetum gnemon L. Seeds on HeLa Cell Lines - Rahmawati, Devi; Ningrum, Dhecella Winy Cintya; Kenyori, Ivana Kinanti; Febriansah, Rifki; Octavia, Melany Ayu; Hermawansyah, Adi (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Cervical cancer results from abnormal cell development in the cervix and is caused by the Human Papillomavirus (HPV). Cancer treatment with chemotherapy drugs has dangerous side effects because it can attack normal cells. Gnetum gnemon L. seeds are known to possess anticancer potential. Therefore, natural ingredients are necessary to develop new cancer drug strategies with minimal side effects. This study aims to determine the anticancer activity of the ethanol fraction of Gnetum gnemon L. Seeds (EFGS) against HeLa cells. The research method used in this study was an identification test to detect compounds from EFGS using the TLC method and the HeLa cell cytotoxic test using the MTT Assay method. The results showed that EFGS contained stilbenoid group compounds based on TLC-Densitometry, with an Rf value of 0.22 cm. The cytotoxic test results on HeLa cells indicated an IC50 value of 784 µg/mL, classifying it as having the potential as a moderate category anticancer agent. Therefore, this study indicates that EFGS can be utilized as a chemopreventive agent.